THE INFLUENCE OF POLITICAL FAKE NEWS ON TIKTOK AND ITS IMPACT ON INTER-ETHNIC RELATIONS IN MALAYSIA - Amri, Ahmad Luqman Mohd Shamsul; Mustazar, Muhammad Aiman Daniel; Hamim, Muhammad Adib Farhan Mohd; Jamri, Mohamad Hafifi; Witianti, Siti (Universitas Padjadjaran, 2025)
TikTok as a platform has become an ideal environment for political discussions and even plays a role in spreading false information. Malaysia, a country with diverse ethnicities, has experienced the impact of viral political misinformation on societal harmony. Thus, this study aims to enhance our understanding of how political misinformation on TikTok can exacerbate ethnic differences in Malaysia by highlighting its potential social implications. The study adopts the Uses and Gratifications Theory as a foundation for developing a framework. A quantitative survey method was employed, with data collected via Google Forms from 407 respondents. Data analysis was conducted using SPSS software. The findings reveal that the majority of respondents are highly aware and knowledgeable about various aspects of political fake news on TikTok. Specifically, understanding of fake news on TikTok is notably high, with an overall mean score of M=4.17, indicating strong comprehension among respondents. Similarly, exposure to political content on TikTok recorded a high average score of M=3.33, reflecting frequent interactions with such material. Furthermore, perceptions of political fake news had an overall mean of M=3.79, showing that respondents generally acknowledge and recognize the presence of misinformation. Lastly, the perceived impact of political fake news on interethnic relations was significant, with a high average score of M=3.99, highlighting concerns about the potential exacerbation of ethnic tensions due to misinformation. These findings underscore the critical need to address the spread of political fake news to mitigate its adverse effects on social cohesion.